Evaluación de los procesos financieros para establecer la liquidez del centro de Acopio J&M del periodo 2019 -2020 - Navarrete Molineros, Luz Evelyn (2021)
Financial processes have been very helpful when evaluating the capital of a company, based on this, why is it necessary? Well, this depends on whether a company can remain standing, since the liquidity of a company is what helps to pay the debts that it has, either to make short and long-term payments, it is then that with this in mind, we can take action plans in case their index is low, in order to meet the appropriate conditions for the company to be sustainable with its payments and profits, so that in the end they can give a good image and I will be able to persevere in the market. This investigation will help us to determine whether the current liquidity applied to the J & J & M collection center, during the 2019-2020 period, has been feasible or not, if it is, to be able to recommend that the process be maintained at that rate or otherwise, recommend considering another strategy to solve this.